2006
DOI: 10.1007/s00203-006-0124-6
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of nodulation genes and symbiotic properties of Genista tinctoria bradyrhizobia

Abstract: Pairwise comparisons of Genista tinctoria (dyer's weed) rhizobium nodA, nodC, and nodZ gene sequences to those available in databanks revealed their highest sequence identities to nodulation loci of Bradyrhizobium sp. (Lupinus) strains and rhizobia from other genistoid legumes. On phylogenetic trees, genistoid microsymbionts were grouped together in monophyletic clusters, which suggested that their nodulation genes evolved from a common ancestor. G. tinctoria nodulators formed symbioses not only with the nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 35 publications
5
27
1
Order By: Relevance
“…Notably, nodA clade II comprises bradyrhizobia isolated from other Genisteae species and from serradella species, which corroborates cross-inoculation data (19,28,42). Similar grouping was observed in phylogenies of nodC and nifH genes (17,48,49), giving rise to the new biovar genistearum for Bradyrhizobium strains nodulating Genisteae legumes, which presumably correspond to clade II Bradyrhizobium strains.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Notably, nodA clade II comprises bradyrhizobia isolated from other Genisteae species and from serradella species, which corroborates cross-inoculation data (19,28,42). Similar grouping was observed in phylogenies of nodC and nifH genes (17,48,49), giving rise to the new biovar genistearum for Bradyrhizobium strains nodulating Genisteae legumes, which presumably correspond to clade II Bradyrhizobium strains.…”
supporting
confidence: 80%
“…BIOGEOGRAPHIC PATTERN SHOWN BY nod GENE PHYLOGENIES 3255 II) in nod gene trees (19,28). Furthermore we showed that bradyrhizobia of this clade have become established in acid soils of Western Australia and South Africa following their probably accidental introduction with lupine and serradella seeds (42).…”
Section: Vol 73 2007mentioning
confidence: 61%
See 1 more Smart Citation
“…The phylogeny of symbiotic nod genes has been frequently related to symbiotic performances of rhizobial strains (9,42,50,51). Here, a large diversity of nodC sequences was observed within L. micranthus endosymbionts, which clustered into four symbiovars.…”
Section: Discussionmentioning
confidence: 96%
“…Symbiotic genes (nif and nod) may have evolutionary histories that are different from those of housekeeping genes in rhizobia, and they have been used to estimate the symbiotic properties of rhizobia (Kalita et al, 2006;Laranjo et al, 2008;van Berkum et al, 2007). Fragments of the nifH (nitrogenase reductase; about 680 bp) and nodA (N-acyltransferase; about 600 bp) genes were amplified from CCBAU 85039 T and sequenced directly, with primers nifH-1 and nifH-2 (Eardly et al, 1992) and nodA-1 and nodA-2 (Haukka et al, 1998), respectively.…”
mentioning
confidence: 99%